2015
DOI: 10.1113/jp270057
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory–auxiliary subunits of CLC chloride channel–transport proteins

Abstract: The CLC family of chloride channels and transporters is composed by nine members, but only three of them, ClC-Ka/b, ClC-7 and ClC-2, have been found so far associated with auxiliary subunits. These CLC regulatory subunits are small proteins that present few common characteristics among them, both structurally and functionally, and their effects on the corresponding CLC protein are different. Barttin, a protein with two transmembrane domains, is essential for the membrane localization of ClC-K proteins and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 139 publications
(247 reference statements)
0
16
0
Order By: Relevance
“…Our results provide additional evidence supporting the role of GlialCAM as a subunit for MLC1 or ClC‐2 (Barrallo‐Gimeno et al . ). In vitro and in vivo data have shown that MLC1 expression at the PM depends on GlialCAM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results provide additional evidence supporting the role of GlialCAM as a subunit for MLC1 or ClC‐2 (Barrallo‐Gimeno et al . ). In vitro and in vivo data have shown that MLC1 expression at the PM depends on GlialCAM.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, GlialCAM restricts ClC‐2 localisation to cell–cell junctions and modulates ClC‐2 channel activity (Barrallo‐Gimeno & Estévez, ; Barrallo‐Gimeno et al . ). The latter is accomplished by increasing current amplitudes of ClC‐2, as well as changing the rectification and activation properties of the channel by affecting its common gating (Jeworutzki et al .…”
Section: Introductionmentioning
confidence: 97%
“…Barrallo‐Gimeno and colleagues review the current state of knowledge regarding these auxiliary subunits: (1) Barttin, important for functionality and regulation of CLC‐K channels, (2) GlialCam, which modifies the physiology of its partner, the ubiquitously distributed CLC‐2, and (3) Ostm1, critical for CLC‐7 activity and stabilization (Barrallo‐Gimeno et al . ). Identified from analysis of genes linked to Bartter's syndrome (Birkenhäger et al .…”
mentioning
confidence: 97%
“…To date, Barttin, Ostm1, GlialCAM are the three regulatory-auxiliary subunits of CLC chloride channel that have been identified (64). As an example, for comparison between these regulatory-auxiliary subunits of above mentioned CLC subfamily, Barttin and Ostm1 are required for endoplasmic reticulum exit, while GlialCAM is not necessary (64). Furthermore, recently it has been reported that palmitoylation of Barttin changes CLC-K channels into an active state (65).…”
Section: Voltage-gated Chloride Channelsmentioning
confidence: 99%
“…So far, just three members of CLC family, ClC-Ka/b, ClC-7, and ClC-2, have been suggested to be linked with accessory subunits. To date, Barttin, Ostm1, GlialCAM are the three regulatory-auxiliary subunits of CLC chloride channel that have been identified (64). As an example, for comparison between these regulatory-auxiliary subunits of above mentioned CLC subfamily, Barttin and Ostm1 are required for endoplasmic reticulum exit, while GlialCAM is not necessary (64).…”
Section: Voltage-gated Chloride Channelsmentioning
confidence: 99%